Harriet Tubman : military scout and tenacious visionary : from her roots in Ghana to her legacy on the Eastern Shore - Wiesen, Jean Marie; Daniels, Rita (Pegasus Books, 2025)
A comprehensive overview of Tubman's life and work, co-authored by one of her descendants, Rita Daniels. For all Harriet Tubman's accomplishments and the myriad books written about her, many gaps, errors, and misconceptions of her legendary life persist. As recognitionand tributes to Tubman's remarkable contributions to American history and civil liberty continues to grow, the time is right for a new biography with the involvement of her family, who have been the caretakers and stewards of her legacy for generations.